Soroconversão Atribuível á Vacinação de Bezerras com a Cepa B-19 de Brucella Abortus. - Santos , Alessandro José Ferreira dos (2023)
Bovine brucellosis is a cosmopolitan anthropozoonosis caused by B. abortus, which causes economic losses to the meat and milk production chain. In order to determine the seroconversion coefficient attributable to the vaccination of heifers with B. abortus strain B 19, 330 blood serum samples from 110 heifers with three to eight months of age were analyzed from five properties in the municipality of Araguaína/TO. A randomized trial was carried out with two groups of heifers, intervention and control, each with 55 animals. Day zero (D-0) of the experiment was marked from the first blood collection immediately before vaccination of intervention group heifers. Post-vaccination blood samples were collected on days 7 (D-7), 14 (D-14) and 21 (D-21). The randomized trial was conducted until D-14, when the heifers of the control group were vaccinated with strain B-19. The collection of 55 blood samples in D-21 allowed to repeat the determination of seroconversion on the seventh day post-vaccination with the control group. All serum samples were submitted to the AAT test. Statistical analyzes were performed with WinPepi® software (version 11.43) and the seroconversion coefficient attributable to vaccination was calculated by subtracting the incidence of seroconversion in the intervention group from that of the control group. In D-7 the seroconversion in the intervention group was 94.55% (95% CI [84.88% to 98.86%]) and in the control group it was null (95% CI [0.00% to 6.49 %]). In D-14 the seroconversion in the control group remained null and that of the intervention group was 98.18% (95% CI [90.28% to 99.95%]). In D-21 the seroconversion in the 55 heifers used in the control group vaccinated in D-14 was 100% (95% CI [93.51% to 100%]), but without significant difference (p≤0.05) to the D-7 response of the intervention group. In order to monitor vaccination, FAO recommends that diagnostic tests be performed using AAT within 2 to 3 weeks post vaccination on random sampling of heifers vaccinated with strain B-19, with 80% seroconversion as the parameter. The results of this study allow us to recommend to the SVO that we institute a vaccination audit, with random collection of blood samples from the seventh day on calves declared as vaccinated with strain B-19, using the AAT test as a diagnostic test and considering a minimum coefficient of seroconversion of 75%, aiming at the monitoring of the vaccination process carried out under the technical responsibility of veterinarians enrolled in the State Programs for the Control and Eradication of Brucellosis and Tuberculosis.